2020
DOI: 10.1002/msc.1490
|View full text |Cite
|
Sign up to set email alerts
|

Can radiographic patellofemoral osteoarthritis be diagnosed using clinical assessments?

Abstract: Introduction: The aim of this study was to determine whether participant characteristics and clinical assessments could identify radiographic osteoarthritis (OA) in individuals with clinically diagnosed, symptomatic patellofemoral osteoarthritis (PFOA). Methods: Participant characteristics and clinical assessments were obtained from 179 individuals aged 50 years and over with clinically diagnosed symptomatic PFOA, who were enrolled in a randomised trial. Anteroposterior, lateral, and skyline X-rays were taken … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 38 publications
(74 reference statements)
0
1
0
Order By: Relevance
“…Moreover, in clinical setting, radiographic TF joint is often evaluated with a posterior-anterior (PA) view radiograph from which the PF joint can not be evaluated at all. In addition, clinical assessments and participant characteristics alone cannot be used to diagnose patellofemoral OA [9,10,11]. Since it has been reported that, at least in some phenotypes of knee OA, PF joint changes even precede TF joint changes ([12, 13, 14]), there is a strong need to consider also PF joint when developing new imaging biomarkers to diagnose and monitor knee OA .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in clinical setting, radiographic TF joint is often evaluated with a posterior-anterior (PA) view radiograph from which the PF joint can not be evaluated at all. In addition, clinical assessments and participant characteristics alone cannot be used to diagnose patellofemoral OA [9,10,11]. Since it has been reported that, at least in some phenotypes of knee OA, PF joint changes even precede TF joint changes ([12, 13, 14]), there is a strong need to consider also PF joint when developing new imaging biomarkers to diagnose and monitor knee OA .…”
Section: Introductionmentioning
confidence: 99%